Seed-induced synthesis of multilamellar ZSM-5 nanosheets directed by amphiphilic organosilane. (26th September 2018) - Fan, Chunyang; Wang, Yaquan; Li, Hongyao; Wang, Xiao; Sun, Chao; Zhang, Xu; Wang, Cui; Wang, Shuhai
Abstract : Multilamellar ZSM-5 nanosheets formed by the transformation of ordered MCM-41-like mesophases. Abstract : Multilamellar ZSM-5 nanosheets have been prepared using silicalite-1 as a seed in the presence of commercially available dimethyloctadecyl[3-(trimethoxysilyl)propyl]ammonium chloride (TPOAC). Characterization results show that these ZSM-5 nanosheets stack disorderly forming lamellar aggregates. Besides, there exists abundant interlayer space in these aggregates which penetrates the whole crystals and results in the formation of inter-connected mesopores. The methanol to gasoline (MTG) reaction has been applied as a probe reaction to evaluate the catalytic performance of ZSM-5 nanosheets. Compared with a ZSM-5 zeolite prepared without TPOAC, the multilamellar ZSM-5 nanosheets displayed an extraordinarily long MTG catalytic lifetime with a similar yield of gasoline range hydrocarbons, which could be reasonably attributed to the special morphology of the nanosheets. To reveal the crystallization mechanism of ZSM-5 nanosheets, the crystallization was stopped at different times first at 120 °C and then at 170 °C. The characterization results show that there exists a unique process of MCM-41-like mesophase formation and then transformation to crystalline MFI phases during a certain period of crystallization.